Putting it in simpler terms
Answer:
f ○ g(x) = x and g ○ f(x) = x is the correct composition
Step-by-step explanation:
INVERSE FUNCTIONS: Two functions are said to be inverse of each other if for every y = f(x), there exists a function g(x),
such that x =
= g(y)
Now, here if we need to show tha two functions f(x) and g(x) are inverse functions of each other , then show that for every x:
1. f o g(x) = f(g(x))= x
2. g o f(x) = g(f(x)) = x
If any two functions satisfy these two conditions, then they are inverse of each other.
Answer:
Th answer is C u got it right
Step-by-step explanation:
Answer:
27 pounds
Step-by-step explanation:
You need to multiply 4.5 by 6.
Hope this helps.